Characteristics of Postvaccination Coronavirus Disease 2019 Hospitalizations Prior to Booster Vaccines. (4th February 2022) - Moffa, Matthew A; Shively, Nathan R; Walsh, Thomas L
Abstract: This analysis describes clinical characteristics and outcomes of 128 fully vaccinated patients hospitalized with coronavirus disease 2019 (COVID-19) prior to booster vaccines. We found that 27% were asymptomatic, 52% required intensive care, and 15% died from COVID-19. Most (89.2%) fully vaccinated patients hospitalized with symptomatic COVID-19 were ≥65 years old and/or severely immunosuppressed.